The reality of classroom interaction and interaction on your lesson platform for teachers of the first three grades in light of the (Covid-19) pandemic in Madaba Governorate - Abu Shannar, Ibrahim Ahmad Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of classroom interaction and interaction on your lesson platform for teachers of the first three grades in light of the (Covid-19) pandemic in Madaba Governorate. The descriptive approach was used, and the study sample consisted of (100) male and female teachers from public schools. To achieve the objectives of the study, the researcher prepared a classroom educational interaction scale of (20) items, and a teacher interaction scale on your lesson platform of (21) items. The results of the study concluded: that the total score of the classroom educational interaction scale was average, with an arithmetic mean of (2.28), and statistically significant differences appeared at the level (α ≤ 0.05) in the classroom educational interaction scale according to the gender variable, where the degrees of females were higher than the degrees of males. While there were no statistically significant differences at the level (α≤ 0.05) in the degree of classroom educational interaction among teachers of the first three grades due to the variable number of years of experience and academic qualification, the total degree of the interaction scale on your lesson platform was moderately with an arithmetic mean of (3.64), as Statistically significant differences appeared at the level (α ≤ 0.05) in the interaction scale on your lesson platform according to the gender variable, where the female scores were higher than the male scores. While there were no statistically significant differences at the level (α≤ 0.05) in the degree of interaction on your lesson platform among teachers of the first three grades due to the variable number of years of experience and academic qualification, and it also showed that there is a positive, statistically significant relationship between the degree of classroom educational interaction for teachers of the three grades The first and the degree of their interaction on your lesson platform was (0.77).